Different doses of UV-B radiation affect pigmented potatoes’ growth and quality during the whole growth period - Wu, Xiaojie; Chen, Bicong; Xiao, Jiping; Guo, Huachun (Frontiers in Plant Science, 2023)
UltraViolet- Biological (UV-B) plays an important role in plant growth and the formation of nutrients, especially secondary metabolites. To investigate the phenotypic changes, physiological responses, and internal genes expression of potatoes under enhanced UV-B radiation, two Yunnan native pigmented potatoes varieties named “Huaxinyangyu” and “Jianchuanhong” were exposed to different UV-B doses during whole growth duration. Pearson correlation analysis and principal component analysis showed that the agronomic characters (i.e. plant height, pitch, stem diameter, and root shoot ratio) of plants treated with low dose ultraviolet (T1) did not change significantly compared with the absence of ultraviolet radiation (CK), even unit yield increased slightly; Similarly, under low UV-B radiation, photosynthetic and physiological parameters (photosynthetic rate, stomatal conductance, respiration rate, and transpiration rate) of leaves were significantly increased. In addition, low-dose UV-B treatment promoted the synthesis of tuber nutrients (e.g. phenols, chlorogenic acids, flavonoids, vitamin C, anthocyanins) and increased the expression of structural genes for anthocyanin synthesis. The number of nutrients and gene expression in tubers raised by the “Huaxinyangyu” was the highest at 84 days, and “Jianchuanhong” was the highest at 72 days. However, the higher dose of UV-B radiation (T2) will cause greater damage to the pigmented potatoes plants, making the plants reduce the yield, and significantly reduce the tuber nutrients. This study showed that proper ultraviolet radiation will not harm pigmented potatoes, but also improve their oxidative stress tolerance, increase the structure genes expression of anthocyanins and continuously synthesize beneficial substances to improve the yield and quality of potato tubers.